ANALYSIS OF CHARACTER AND SOCIAL EDUCATION VALUES TOWARD CHILDREN IN NUSSA AND RARA FILM EPISODE 3S - Muh. Haris Zubaidillah; Husin; Nesrin; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Apart from being a means of entertainment, films can also be a means of guidance to the public through the message contained in the film. Therefore, the public must be more careful in choosing films, especially for children, so as not to fall prey to the negative things that come from the films they watch. Nussa and Rara is one of the children's animated films with the Muslim genre that children like. In this animated film there are positive educational values ​​for children. This study aims to analyze the educational values ​​contained in the film Nussa and Rara in one of its episodes entitled 3S (Senyum, Salam, Sapa).This study used library research methods with mass media analysis as the type of research. The results of the study show that there are two types of character education in the films Nussa and Rara episode 3S (Senyum, Salam, Sapa), namely character education and social education. The character education values ​​contained in the animated film are based on the Ministry of Education and Culture's references, namely religious attitude, fond of reading and curiosity. Meanwhile, the social educational values ​​contained in the film are based on Nashih Ulwan's opinion, namely 1) the inculcation of noble psychological foundations, namely piety and brotherly affection. 2) safeguarding the rights of others, namely the teaching of social etiquette.